‘Learning from Home’ as a Form of Social Change in Educational Perspective: Impact and Challenges of the Covid-19 Era - Nurul Yunita; Karim Suryadi; Leni Anggraeni (Universitas Sebelas Maret, 2021)
Social change in the educational field has occurred due to the Covid-19 pandemic. In-person learning is no longer implemented to minimize the impact of the spread of the virus. Due to this fundamental change, children’s education that can be accessed from home has become a necessity. Parents now have a duty to become teachers for their children at home. Such occurrence is the result of the implementation of learning from home, which is supported by online learning. It serves as a panacea for the education sector during the Covid-19 era. Online learning is appealing due to its easy accessibility, wide reach, comfort, and flexibility in terms of participation. However, online learning has its own shortcomings. Among others, it limits interaction with others, making students feel isolated from their teachers and classmates. This article uses narrative review to analyze and elaborate on 30 journals that discuss learning from home, in terms of the impact of social change on students and the experience of parents.